FACTORS AFFECTING PRODUCTIVITY OF PLANTATION EMPLOYEES AT PT. GREAT GIANT PINEAPPLE, CENTRAL LAMPUNG - Ayurei Nuralfya; Wahyu Budi Priatna; Burhanuddin Burhanuddin (Socio-Economics/Agribusiness Department, 2023)
The movement of a company can’t be separated from resources owned by the company. In this case, the success of a company is strongly supported by the human resources in it. Good work management in a company can be reflected in the creation of a balance between labor productivity and the demands of the company's progress. Therefore, this research aims to analyze internal and external factors related to the productivity of plantation employees in the agroindustrial company engaged in the production and largest pineapple exporter in Indonesia, PT. Great Giant Pineapple. This research also aims to analyze factors most influence productivity of plantation employees. This research was conducted by taking data from 220 respondents of plantation employees using the convenience technique method. Furthermore, data processing and validity and reliability test were carried out using SPSS 17 Ver 25.0, and quantitative tests were processed using SmartPLS to analyze the structural equation model using SEM-PLS. Based on the result, there are six factors that influence the productivity of plantation employees: motivation, competence, work environment, discipline, work quality, and incentive, which are then tested on employee productivity factors. The factor of motivation, competence, discipline, work quality, and incentive have a significant effect on the productivity of employees, while the work environment factor has an insignificant effect on the productivity of employees.